Water Quality of Groundwater in Selected Wells in Zubair Area, Basra City - Towfik, Saad Muhi; Hammadi , Adnan Jassam (Iraqi Journal of Science, 2020)
Zubair area is located at the extreme part of the south of Iraq and represents the southern part of the western desert, bounded by the north latitudes 30o05'-30o25' and east longitudes 47o30'- 47â—¦55'. Groundwater is a major natural resource in the study area because no perennial river exists. Groundwater from twenty wells in the study area were analyzed in order to determine some of chemical variables such as major cations (Ca+2, Mg+2 ,Na+ ,K+ ) and major anions (CL- ,SO4-2 ,HCO3- ,CO3-2 ,NO3-) along with several physical variables such as hydrogen ion concentration (pH) , total dissolved solids (TDS), and electrical conductivity (EC). Hydro-chemical analysis showed that the groundwater of the study area is excessively mineralized, depending on the relation between EC and mineralization. Depending on total hardness (TH), all samples were with very hard water. High chloride concentration in the groundwater of the study area may be an indicator of pollution by sewage and agriculture fertilizers. The increase in flow length of the groundwater in the study area would change the water quality from bicarbonate to sulfate and chloride. The predominant cations recorded are calcium and magnesium along with chloride from the anions, so that the water type is Ca-Mg-CL for most samples. The water wells studied are not suitable for drinking purposes of humans. Depending on TDS and EC values, the water samples are not suitable for irrigation according to FAO 1997 classification. However, the results also revealed an excellent water class depending on Na percentage (Na%) and EC according to Todd 1980 classification for irrigation water. Also, an excellent water class (S1) for agriculture was recorded depending on SAR classification of Subramain, 2005.